Investigations of LiP(SiMe2CH2SiMe3)–PtBu2, the Surprising Byproduct in the Metalation of (Me3Si)2P–PtBu2. Issue 46 (14th December 2017) - Sattler, Ewald; Szilvási, Tibor; Matern, Eberhard; Bombicz, Petra; Gamer, Michael; Okrut, Alexander; Kovács, Ilona
Abstract : During the metalation reaction of (Me3 Si)2 P–P t Bu2 with n BuLi, a byproduct with the sum formula Li(thf) n P(SiMe2 CH2 SiMe3 )–P t Bu2 (2, n = 2.7–1) was detected. The formation of the unexpected substituent SiMe2 CH2 SiMe3 was investigated, a possible reaction mechanism based on DFT calculations established, and the compound synthesized following an independent route. Compound2 eliminated thf in vacuo to yield the dimeric [Li(thf)P(SiMe2 CH2 SiMe3 )–P t Bu2 ]2 (2a ). Exchange of thf with tmeda [Me2 N(CH2 )2 NMe2 ] in2 led to the solvent‐separated ion pair [Li(tmeda)2 ] + [(SiMe2 CH2 SiMe3 )P–P t Bu2 ] – (4 ). The solid‐state structures of2a, 4, and the contact ion pair Li(thf)(tmeda)P(SiMe2 CH2 SiMe3 )–P t Bu2 (5 ) were determined by single‐crystal X‐ray diffraction analysis. Extensive variable‐temperature multinuclear NMR studies were carried out to elucidate the structures of these compounds in solution and to compare them with the solid‐state structures. Abstract : The title compound was isolated as a byproduct in the reaction of (Me3 Si)2 P–P t Bu2 with n BuLi, then independently synthesized and structurally characterized. In the solid state Li(L) n P(SiMe2 CH2 SiMe3 )–P t Bu2 forms a dimer (L = thf, n = 1) or monomers with solvent‐separated (L = tmeda, n = 2) or contact ion pairs (L = thf + tmeda, n = 1 + 1). A possible mechanism of formation is discussed.